Alih Kode dan Campur Kode pada Percakapan Keseharian di Lingkungan Fakultas Syariah dan Ekonomi Islam - Syukriati A (El-Tsaqafah : Jurnal Jurusan PBA, 2019)
This study aims to examine the problems of form, type, purposeand factors that cause the process of code switching and code mixing inthe daily conversations of lecturers and staff at the Faculty of Sharia andIslamic Economics. This type of research is qualitative descriptive research.Data collection in this study uses skillful listening techniques while dataanalysis uses extralingual equivalent methods. The research location wasat the Faculty of Sharia and Islamic Economics IAIN Mataram. While theobject of research is daily conversation at the Faculty of Sharia and IslamicEconomics IAIN Mataram. The results of the findings of this study are theform of code switching and code mixing found in the form of words, phrasesand clauses. The type of code transfer that is found is internal code switching(inner code-switch) and the type of code mixing found in the form of mixingcode into (inner mixing-code). While the purpose of code switching is foundin the form of: affirmation, debilitating, certainty, curiosity, explanation,quips, suggestions, offers and notifications. The purpose of the code mixwas found in the form of: respect, affirmation, ambiguity, wonder, specific,anger, culture, information, curiosity, prohibition and appeal. Factors thatcause code switching are: opposed to speaking and the presence of thirdspeakers. While the causes of interfering code are: desire factors to explain,variety identification factors and role identification factors.